Pediatric Submandibular Abscess: Diagnostic Challenges and Comprehensive Management – A Literature Review - Virjinea Hawani Rein; Arroyan Wardhana; Hastuti Rahmi (Medical and Health Journal, 2026)
Submandibular abscess in children is a rare deep neck space infection but can be fatal if diagnosis and management are delayed. Most cases (70–85%) originate from odontogenic infections of the mandibular molars, with Staphylococcus aureus and Streptococcus viridans as the predominant pathogens. This article reviews the etiology, early diagnosis, and management of pediatric submandibular abscesses based on recent literature (2020–2025) from Google Scholar, PubMed, and ScienceDirect. Anatomical and immunological differences in children lead to faster infection spread with nonspecific early symptoms; therefore, careful clinical examination and the use of CT scans or ultrasonography are crucial for early diagnosis. Management includes airway stabilization, culture-based broad-spectrum antibiotics, and timely surgical drainage. Multidisciplinary collaboration among dentists, ENT specialists, and pediatric anesthesiologists is essential to reduce morbidity and mortality. Prospective studies are needed to evaluate the effectiveness of minimally invasive approaches and current antibiotic resistance patterns in children. Early diagnosis, rational therapy, and interdisciplinary cooperation remain the key factors in achieving successful outcomes in pediatric submandibular abscess management.